Synthetic Sorbent Materials Based on Metal Sulphides and Oxides - Sofronov, D.S (Taylor & Francis, 2021)
This monograph focuses on development of inorganic nanomaterials for removal of metallic species from the aqueous environment. General synthetic methods to prepare such materials are lacking. This book investigates problems of controlled synthesis of these materials and the effect of their morphological characteristics on their sorption capacity. This book is of interest to researchers and scientists working with inorganic synthesis and properties of sorption materials.